The Effectiveness of COVID-19 Countermeasure Policy Implementation in Seven ASEAN Countries - Sulistiadi, Wahyu; Rahayu, Sri (UI Scholars Hub, 2020)
COVID-19, which has spread to almost all countries in the world, force country's leaders to issue COVID-19 countermeasures policy that is the most effective and suitable for their country. The various ways to implement the policy depend on the COVID-19 impact that arises in the country. This study describes the implications of national policies related to COVID-19 case fatality rates up to 29 April 2020 in 7 ASEAN countries. We use analytical descriptive method on COVID-19 data that has been published in online media. The achievement on the implementation of national policy in overcoming COVID-19 in some countries provide new perspectives for all other countries in maintaining and improving relations between the government and its citizens to implement the most effective way in reducing mortality (Case Fatality Rate).